PENGARUH KOMPETENSI PADA PENERAPAN PERLAKUAN AKUNTANSI ASET BERSEJARAH - Suri Awya Wambarika, I Gusti Ayu Cintya; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
This research aims to determine the effect of education, work experience, and understanding of the standards on the application of the accounting treatment of historical assets. Research conducted at the Bali Provincial Cultural Office with a total sample of 35 employees. The method used purposive sampling and multiple linear regression analysis. Based on the analysis no influence levels of education and work experience in the application of the accounting treatment of historical assets. This shows the level of education and a period of work does not affect the application of accounting treatment of historical assets. Meanwhile, the results of the analysis found that the understanding of the accounting standard affects the application of the accounting treatment of historical assets. This shows the growing understanding of managers in accounting standards will improve the application of the accounting treatment of historical assets.
Keywords: historical assets, level of education, work experience, understanding of accounting standards